The six days of voluntary fasting in Syawal and its significance to the personality of Muslims - Che Sulaila Che Harun,; Syaidatun Nazirah Abu Zahrin,; Khairul Anwar Mastor, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The six days fasting in the month of Syawal is a voluntary fasting after the 30 days of obligatory fasting in the month of Ramadan. The purpose of this study was to determine the effects of sixday fasting in the month of Syawal on the changes of personality among Muslims. A total of 111 participants comprised of students from Universiti Kebangsaan Malaysia (UKM) and Universiti Malaysia Kelantan (UMK) took part in this study. All participants were Muslims, consisting 91 women and 20 men with age range of 20 years to 53 years old. The analysis method used was multilevel modeling using Hierarchical Linear Modeling (HLM) version 7.0. The LHM was used to test all the hypotheses of the study. The objective of the study was to identify the impact of the Syawal voluntary fasting on the personality change. The findings of this study showed that the quality of Syawal voluntary fasting gives effect to the change of personality which bring significant relationship with both positive and negative personalities. Hence, it can be concluded that the six days voluntary fasting in the month of Syawal contributed to the changes of personality among Muslims.